RANCANG BANGUN SISTEM INFORMASI POSYANDU CENDANA DI KELURAHAN KAHURIPAN KOTA TASIKMALAYA - Hani Rubiani; Eddy Samsoleh; Sulidar Fitri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
Integrated Service Post is one form of community-based health efforts organized by and for the community that aims to empower the community and provide convenience to the community. Communities targeted by Posyandu include pregnant women, breastfeeding mothers, women of childbearing age, men of childbearing age, infants and toddlers in obtaining essential health services. The data on the results of the Posyandu activities are recorded in the administration book by the Posyandu cadres. Many Posyandu still records manual data; that is, the data is written in administrative books, which causes cadres to find it challenging to monitor all participants from time to time and make it challenging to report by the Health Office standards. Including one that occurred at the Cendana Posyandu as a partner located in 17, Kahuripan Village, Tawang District, Tasikmalaya City. The solution to this problem is to propose applying an information system that can facilitate data management and administration of partner posyandu, especially in the availability of effective and efficient data. This activity aims to implement the posyandu information system at the Cendana posyandu to improve the quality and accuracy of data management. The result of this activity is the availability of a Posyandu information system in a systematic, effective and efficient manner. It can make it easier for cadres to monitor the development of mothers and toddlers from time to time and facilitate report generation.